ANALISIS YURIDIS ATAS AKTA NOTARIS TERKAIT DENGAN PENGIKATAN JUAL BELI HAK ATAS TANAH DENGAN CICILAN - WANDA LUCIA (PREMISE LAW JURNAL, 2013)
ABSTRACT One of methods to of obtain a piece of land is buying and selling. Based on article 1358 of the Civil Code, buying aid selling is considered valid when the two parties have agreed on the good and the prices although the goods have not been received and paid by the buyers. In this case, the purchase agreement on the land rights wich is done with installment is used as the preliminary agreement in the practice of a Notary. The process of buying and selling by a sales agreement with installment has not yet been the action of buying and selling and valid as it is intended by the the national land act. However, it is the follow up from the legal act of the sales agreement wich is still in process because it should fulfill the requirement of transferring title, such as the object has not yet been paid off. This is commonly found in the practice of a Notary, especially in the implementation of the buying and selling process; in this case the parties concerned should be protected. Keywords: Sales Agreement, Land Rights, Installment